Mercury accumulation and biomagnification in the barn owl (Tyto alba) food chain - Sabnam Mahat; Bettina Almasi; Ingrid S. Kjelsen; Dan S. Marmet; Gerald Heckel; Alexandre Roulin; Andreas M. Buser; Adrien Mestrot (Journal of Hazardous Materials, 2025)

Spatio‐temporal shift in body size and plumage coloration is associated with the magnitude of climate change in a cosmopolitan owl - Andrea Romano; Gaëlle Florent; Andrea Novelli; Robin Séchaud; Alexandre Roulin (Journal of Biogeography, 2024)
Aim Climatic gradients shape geographic variation in phenotypic traits that are involved in animal thermoregulation. Therefore, increasing temperatures under global warming are expected to cause change over time in traits that show predictable spatial patterns according to environmental clines (body and appendage size, tegument coloration), as well exemplified by biogeographic rules and shown by increasing literature at a local scale. However, whether temporal shifts in phenotypic traits vary spatially according to the magnitude of the change in local climatic conditions is still unknown. Location World. Taxon Barn owl species complex ( Tyto alba group). Methods By using thousands of museum specimens collected across the globe from 1901 to 2018, we calculated within‐population change over time in wing length, bill length and melanin‐based plumage coloration and examined whether these trends differed across geographic regions, latitudes and gradients of climate changes. Results We showed that populations exposed to an increasing warmer climate were subjected to a more marked decrease in body size, as gauged by wing length, and also absolute bill length that displayed a similar, although less steep, pattern of shrinking over time. In addition, phaeomelanin‐based ventral plumage colour has become paler in regions where the climate changed into warmer and drier, and darker where both temperature and precipitation increased. Main Conclusions These trends are generally coherent with the predictions based on Bergmann's and Gloger's rules, but not Allen's rule, and suggest that temporal shifts in body size and tegument colour depend on the magnitude of the alteration in climatic conditions, with populations living in regions where the climate has changed the most that are subjected to more marked phenotypic changes. Spatio‐temporal variation in climate has driven within‐species phenotypic clines, and it is expected to increase differences among populations according to the predicted further climate change.

Competitive interactions of two sympatric raptors affecting their spatial distribution in an island environment - Nicolaos I. Kassinis; Savvas Zotos; Iris Charalambidou; Alexandre Roulin; Ioannis N. Vogiatzakis (Journal of Ornithology, 2024)

Melanin-based plumage coloration and melanin content in organs in the barn owl - Alexandre Roulin; Sylvain Dubey; Shosuke Ito; Kazumasa Wakamatsu (Journal of Ornithology, 2024)
Although the evolutionary ecology of melanin pigments and melanin-based coloration has been studied in great details, particularly in birds, little is known about the function of melanin stored inside the body. In the barn owl Tyto alba , in which individuals vary in the degree of reddish pheomelanin-based coloration and in the size of black eumelanic feather spots, we measured the concentration in melanin pigments in seven organs. The eyes had by far the most melanin then the skin, pectoral muscle, heart, liver, trachea, and uropygial gland. The concentration in eumelanin was not necessarily correlated with the concentration in pheomelanin suggesting that their production can be regulated independently from each other. Redder barn owls had more pheomelanin in the skin and uropygial gland than white owls, while owls displaying larger black feather spots had more eumelanin in the skin than small-spotted owls. More data are required to evaluate whether melanin-based traits can evolve as an indirect response to selection exerted on melanin deposition in organs.

Island volcanism predicts pheomelanin‐based plumage colouration in a cosmopolitan raptor - Andrea Romano; Robin Séchaud; Luca Montanarella; Alexandre Roulin (Journal of Biogeography, 2023)
Aim Pheomelanin is a pigment responsible for yellowish‐to‐reddish colours of vertebrate teguments. Its biosynthesis is favoured under high concentration of intracellular thiols, which, in turn, can depend on the environmental exposure to sulphur. Thus, pheomelanin production should be more intense and frequent in environments characterized by high level of sulphur, such as volcanic regions. In this study, we aimed at addressing this hypothesis by investigating variation in plumage colour of insular populations of the cosmopolitan barn owl ( Tyto alba species complex) according to the presence of soils of volcanic origin (i.e. andosols) and recent volcanic activity. Location World. Taxon Barn owl species complex. Methods We measured plumage colouration of more than 2000 museum specimens from 50 islands and archipelagos worldwide. We then compared plumage colouration between populations living on volcanic (i.e. where andosols and/or recent volcanic activity are present) and non‐volcanic islands/archipelagos. Results Consistently with the prediction, plumage colouration is significantly darker (i.e. pheomelanic) on islands/archipelagos where andosols and/or recent volcanic activity are present than absent, although this environmental factor explains a small fraction of plumage colour variability across islands ( Main Conclusions Because excessive intracellular levels of thiols can be toxic, pheomelanin synthesis may function as a mechanism keeping these compounds below the toxicity threshold and limiting their detrimental effects on physiology. Darker plumage may also be favoured because it promotes background matching against the dark environment typical of volcanic islands (dense vegetation cover and/or dark soil). Our results add to the little evidence that the environmental exposure of compounds that are involved in melanin biosynthesis can affect animal pigmentation and suggest that soil composition may be a factor that affects melanogenesis, possibly contributing to generate spatial variation in pheomelanin‐based traits in animals.

Genomic consequences of colonisation, migration and genetic drift in barn owl insular populations of the eastern Mediterranean - Ana Paula Machado; Alexandros Topaloudis; Tristan Cumer; Eléonore Lavanchy; Vasileios Bontzorlos; Renato Ceccherelli; Motti Charter; Nicolaos Kassinis; Petros Lymberakis; Francesca Manzia; Anne‐Lyse Ducrest; Mélanie Dupasquier; et al. (Molecular Ecology, 2022)
The study of insular populations was key in the development of evolutionary theory. The successful colonisation of an island depends on the geographic context, and specific characteristics of the organism and the island, but also on stochastic processes. As a result, apparently identical islands may harbour populations with contrasting histories. Here, we use whole genome sequences of 65 barn owls to investigate the patterns of inbreeding and genetic diversity of insular populations in the eastern Mediterranean Sea. We focus on Crete and Cyprus, islands with similar size, climate and distance to mainland, that provide natural replicates for a comparative analysis of the impacts of microevolutionary processes on isolated populations. We show that barn owl populations from each island have a separate origin, Crete being genetically more similar to other Greek islands and mainland Greece, and Cyprus more similar to the Levant. Further, our data show that their respective demographic histories following colonisation were also distinct. On the one hand, Crete harbours a small population and maintains very low levels of gene flow with neighbouring populations. This has resulted in low genetic diversity, strong genetic drift, increased relatedness in the population and remote inbreeding. Cyprus, on the other hand, appears to maintain enough gene flow with the mainland to avoid such an outcome. Our study provides a comparative population genomic analysis of the effects of neutral processes on a classical island‐mainland model system. It provides empirical evidence for the role of stochastic processes in determining the fate of diverging isolated populations.

Unexpected post‐glacial colonisation route explains the white colour of barn owls ( Tyto alba ) from the British Isles - Ana Paula Machado; Tristan Cumer; Christian Iseli; Emmanuel Beaudoing; Anne‐Lyse Ducrest; Melanie Dupasquier; Nicolas Guex; Klaus Dichmann; Rui Lourenço; John Lusby; Hans‐Dieter Martens; Laure Prévost; et al. (Molecular Ecology, 2022)
The climate fluctuations of the Quaternary shaped the movement of species in and out of glacial refugia. In Europe, the majority of species followed one of the described traditional postglacial recolonization routes from the southern peninsulas towards the north. Like most organisms, barn owls are assumed to have colonized the British Isles by crossing over Doggerland, a land bridge that connected Britain to northern Europe. However, while they are dark rufous in northern Europe, barn owls in the British Isles are conspicuously white, a contrast that could suggest selective forces are at play on the islands. Yet, our analysis of known candidate genes involved in coloration found no signature of selection. Instead, using whole genome sequences and species distribution modelling, we found that owls colonised the British Isles soon after the last glaciation, directly from a white coloured refugium in the Iberian Peninsula, before colonising northern Europe. They would have followed a hitherto unknown post‐glacial colonization route to the Isles over a westwards path of suitable habitat in now submerged land in the Bay of Biscay, thus not crossing Doggerland. As such, they inherited the white colour of their Iberian founders and maintained it through low gene flow with the mainland that prevents the import of rufous alleles. Thus, we contend that neutral processes probably explain this contrasting white colour compared to continental owls. With the barn owl being a top predator, we expect future research will show this unanticipated route was used by other species from its paleo community.

Nidicolous beetle species richness is driven by Barn Owl’s nests occupancy and landscape structure - Vivien Cosandey; Robin Séchaud; Paul Béziers; Yannick Chittaro; Andreas Sanchez; Alexandre Roulin (Journal of Ornithology, 2021)
Bird nests are specialized habitats because of their particular composition including nest detritus and bird droppings. In consequence, they attract a specialized arthropod community considered as nidicolous, which includes species only found in bird nests (strictly nidicolous) or sometimes found in bird nests (facultatively nidicolous). Because the factors influencing the entomofauna in bird nests are poorly understood, in autumn 2019, we collected nest material in 86 Barn Owl ( Tyto alba ) nest boxes. We investigated whether the invertebrate species richness was related to Barn Owl nest box occupancy, the density of available nest boxes and the landscape structure. We found 3,321 nidicolous beetle specimens belonging to 24 species. Species richness of strictly nidicolous beetles was 2.7 times higher in nest boxes occupied by a family of Barn Owls the previous spring compared to unoccupied nest boxes. It was also higher in sites that were more often occupied by Barn Owls in the five previous years and in areas surrounded by a higher proportion of crop fields. For facultatively nidicolous beetles, the density of Barn Owl nest boxes enhanced the species richness. In conclusion, our study suggests that the strictly nidicolous beetles benefit from occupied nest boxes of Barn Owls, whereas facultatively nidicolous beetles look for nest boxes independently of whether Barn Owls occupy them. Our study highlights the importance of bird nests for a suite of invertebrates.

Evolution of wing length and melanin‐based coloration in insular populations of a cosmopolitan raptor - Andrea Romano; Robin Séchaud; Alexandre Roulin (Journal of Biogeography, 2021)
Aim Insular populations face different conditions than those living on continents, thus, resulting in the evolution of typical insular phenotypes, like smaller body sizes or reduced colourations. However, the generality of the so‐called “island rule” has been questioned, and intraspecific analyses on the effects of insularity on cosmopolitan species are lacking. Here, we tested the predictions of the island rule in the cosmopolitan common barn owl group. Location World. Taxon Barn owl species complex. Methods We compared wing and bill length, as well as melanin‐based plumage traits, between thousands of insular and continental barn owls living in the Afro‐Palearctic region ( Tyto alba ), in the Americas ( Tyto furcata ) and in Australasia ( Tyto javanica ). We also tested whether the difference between insular and continental populations in these phenotypic traits varies among islands/archipelagos of different size and isolation. Results In all the regions, we found differences between insular and continental owls in all the traits but bill length, with insular populations convergently evolving shorter wings and paler colourations. In addition, the difference in wing size between insular and continental populations is particularly marked on small and remote island systems, while melanin‐based traits are less expressed especially on large islands. Main conclusions We thus provide unprecedented evidence that insular conditions drive predictable phenotypic variations, even at the intraspecific level in different biogeographic regions, possibly promoting speciation events. In addition, our results also indicate that selective advantages of a given colouration can arise as the by‐product of positive selection on individuals displaying phenotypic traits which can favour island colonization and are genetically linked to melanization.

Movement ecology, breeding, diet, and roosting behavior of barn owls (Tyto alba) in a transboundary conflict region - Gabriel Rozman; Ido Izhaki; Alexandre Roulin; Motti Charter (Regional Environmental Change, 2021)

Generalized evidence for Bergmann’s rule: body size variation in a cosmopolitan owl genus - Andrea Romano; Robin Séchaud; Alexandre Roulin (Journal of Biogeography, 2021)
Aim The eco‐geographical Bergmann's rule predicts that animals have smaller body size in warmer regions than in cold environments because of thermoregulatory reasons. Although this rule has been widely investigated, intraspecific analyses on cosmopolitan taxa are rare. We examined whether geographical variation in wing length, a proxy of body size, shows a Bergmannian pattern and can be explained by three mechanisms known to affect animal body size (heat conservation, resource availability and starvation resistance) in seven species of nocturnal raptors of the genus Tyto . Location World. Taxon Genus Tyto . Methods We measured wing length of 9,033 museum specimens covering the entire distributional range of each species and linked it with geographical (absolute latitude, elevation) and climatic predictors associated with heat conservation, resource availability and starvation resistance hypotheses of spatial variation in body size. Results All the species show a trend of increasing wing length with increasing latitude and/or elevation, and in five of them either or both geographical predictors are statistically significant. In all the species showing a Bergmannian pattern, wing length significantly decreases with temperature, thus supporting the heat conservation hypothesis. Conversely, we found less generalized support for the other hypotheses, although in some species significant trends between wing length and proxies of climatic seasonality and/or primary productivity emerged. Main conclusions Consistent clines in body shrinking in warm environments are observed in species living in different continents at different latitudinal and temperature ranges, as well as exploiting different habitats. These findings thus support the hypothesis that body size is, at least partly, selected for heat maintenance depending on the thermal environment, even in nocturnal species which are not directly exposed to solar radiation. However, different selective pressures may also have concomitantly acted to promote body size evolution in this bird group.

Global biogeographical patterns in the diet of a cosmopolitan avian predator - Andrea Romano; Robin Séchaud; Alexandre Roulin (Journal of Biogeography, 2020)
Aim The investigation of biogeographical patterns in the diet of widely distributed predators is essential to understand their ecology, life history traits and local adaptations. However, it is particularly challenging because of their wide distribution, broad trophic spectra and high ecological plasticity. Here, we described patterns of trophic ecology in a cosmopolitan nocturnal raptor, the common barn owl group, from a biogeographical perspective. We then compared variation in diet between barn owls living in the Americas ( T. furcata ), and those inhabiting Europe, Middle‐East and Africa ( T. alba ), thus hunting on different assemblages of prey types. Location World. Taxon Barn owl species complex. Methods We reviewed 790 studies reporting diet information of 971 locations (3,733,902 individual vertebrate prey), and investigated the variation in different diet parameters, reflecting taxonomic diversity, size of the prey and frequency of certain prey types according to geographical and climatic variables. Results While confirming that the barn owl is a selective mammal hunter with variable taxa constituting its staple food in different regions, we also found significant geographical and climatic trends in several diet parameters. Although prey composition differed among continents, most of the patterns, including an increase in proportion of mammal prey in cold environments, an increase in diet diversity with elevation, a decrease in small prey consumption from high to low latitudes and at increasing temperature, and a decrease in rodent predation in humid habitats, were similar between T. furcata and T. alba . A strong island effect was observed for all diet parameters. Main conclusion Our results indicate a generalized pattern of variation in barn owl diet across biogeographical regions, suggesting that similar prey communities occur in habitats with comparable ecological conditions and/or that different barn owl populations living in similar climate convergently evolved similar food preferences and hunting strategies.

Geographical variation in bill size provides evidence for Allen’s rule in a cosmopolitan raptor - Andrea Romano; Robin Séchaud; Alexandre Roulin (Global Ecology and Biogeography, 2020)
Aim Avian beak morphology is a good example of how anatomical structures have evolved in response to different selective pressures, such as diet and vocalizations, but also thermoregulation. The last of these functions was neglected until recently, but convincing evidence has been provided regarding the capacity of birds to regulate heat dissipation through their highly vascularized bills. According to this adaptive function and coherently with the ecogeographical “Allen's rule”, which predicts smaller body appendages in colder climates, large beaks should be favoured in warm environments. Here, we tested this prediction in the cosmopolitan common barn owl group. Location World. Time period 1809–2017. Major taxa studied Tyto alba species complex. Methods We analysed the variation in bill length relative to body size according to temperature, latitude and elevation in 7,619 barn owls. The specimens were collected by 140 museums and represent three distinct evolutionary lineages that occur in geographically separated regions and cover the entire distributional range of the species complex: the Afro‐Palaearctic Tyto alba , the Australasian Tyto javanica and the American Tyto furcata . Results In the three lineages, the bill becomes larger with increasing temperature. This convergent pattern of evolution of smaller bills in colder climates is associated with a latitudinal variation in temperature, because small‐billed individuals occurred at higher latitudes than conspecifics living closer to the Equator. Moreover, in T. furcata , large‐billed birds mostly occurred at lower elevations closer to the Equator, with bill length decreasing progressively with concomitant increase in latitude and elevation. Discussion These findings provide evidence for the repeated evolution of bill size on a global scale that is compatible with Allen's rule. These results suggest a role of the bill as a potential heat‐exchange surface in nocturnal raptors, which are not directly exposed to solar radiation and whose bill shape evolved primarily to hunt and consume animal prey.

Lack of statistical power as a major limitation in understanding MHC‐mediated immunocompetence in wild vertebrate populations - Arnaud Gaigher; Reto Burri; Luis M. San‐Jose; Alexandre Roulin; Luca Fumagalli (Molecular Ecology, 2019)
Disentangling the sources of variation in developing an effective immune response against pathogens is of major interest to immunoecology and evolutionary biology. To date, the link between immunocompetence and genetic variation at the major histocompatibility complex (MHC) has received little attention in wild animals, despite the key role of MHC genes in activating the adaptive immune system. Although several studies point to a link between MHC and immunocompetence, negative findings have also been reported. Such disparate findings suggest that limited statistical power might be affecting studies on this topic, owing to insufficient sample sizes and/or a generally small effect of MHC on the immunocompetence of wild vertebrates. To clarify this issue, we investigated the link between MHC variation and seven immunocompetence proxies in a large sample of barn owls and estimated the effect sizes and statistical power of this and published studies on this topic. We found that MHC poorly explained variation in immunocompetence of barn owls, with small‐to‐moderate associations between MHC and immunocompetence in owls (effect size: .1 ≥ r ≤ .3) similar to other vertebrates studied to date. Such small‐to‐moderate effects were largely associated with insufficient power, which was only sufficient (>0.8) to detect moderate‐to‐large effect sizes ( r ≥ .3). Thus, studies linking MHC variation with immunocompetence in wild populations are underpowered to detect MHC effects, which are likely to be of generally small magnitude. Larger sample sizes (>200) will be required to achieve sufficient power in future studies aiming to robustly test for a link between MHC variation and immunocompetence.

Climate‐driven convergent evolution of plumage colour in a cosmopolitan bird - Andrea Romano; Robin Séchaud; Alexandre H. Hirzel; Alexandre Roulin (Global Ecology and Biogeography, 2019)
Aim The investigation of phenotypic diversity across geographical gradients is pivotal to understanding the evolution and adaptive functions of alternative phenotypes. The aim of the present study was to investigate whether the polymorphism in ventral plumage colouration observed in the cosmopolitan common barn owl group is determined by climatic factors, such as temperature and rainfall, consistent with Gloger’s and Bogert’s biogeographical rules. Location World. Time period 1809–2017. Major taxa studied Tyto alba species complex. Methods We analysed the variation in heritable melanin‐based plumage colour according to annual temperature and rainfall in 9,110 individuals of the cosmopolitan barn owl, with three distinct evolutionary lineages representing its entire distribution range: the Afro‐European Tyto alba , occurring between Scandinavia and South Africa, the American Tyto furcata , found from southern Canada to Patagonia, and the Australasian Tyto javanica , living between the Himalayan Plateau and Tasmania. Results Although the geographical distribution of colour morphs is heterogeneous among the lineages, in all of them plumage colour becomes darker with increasing annual rainfall, indicating a convergent selection of darker morphs in humid habitats possibly to improve camouflage against the dark environment and/or to repel water more efficiently. Moreover, in T. alba and T. furcata , melanization increases at decreasing temperature, suggesting its possible role in thermoregulation. Discussion These findings provide convincing evidence of repeated evolution of similar body colouration patterns at a worldwide scale compatible with the main biogeographical rules, while emphasizing the possible role of melanin‐based traits in animal adaptation to climate change.

The Rocky Mountains as a dispersal barrier between barn owl ( Tyto alba ) populations in North America - Ana Paula Machado; Laura Clément; Vera Uva; Jérôme Goudet; Alexandre Roulin (Journal of Biogeography, 2018)
Aim Geological barriers within a species range play a key role in shaping patterns of genetic variation by restricting gene flow. Mountain ranges are particularly imposing barriers responsible for creating genetic differentiation across multiple taxa, from small amphibians to large mammals and birds. Here, we examined the population structure of North American barn owls ( Tyto alba ) and investigated whether the Rocky Mountains influence gene flow and dispersal at the continental scale. Location Continental North America. Methods We collected 292 museum samples covering the species range, genotyped them at 20 microsatellite markers and sequenced 410 bp of the mitochondrial gene ND 6 . Population and landscape genetics tools were used to study range‐wide patterns of structure and identify gene flow barriers. Ring recapture data were also analysed to investigate individual movement patterns and frequency of exchanges between both sides of the Rocky Mountains. Results We found faint overall genetic structure, which is consistent with barn owl's high mobility across its continuous range. Nonetheless, we identified two distinct genetic groups on the western and eastern regions of the Rocky Mountains with a likely contact point through the narrow southern pass between them and the Sierra Madre Occidental in Mexico. Accordingly, most recaptured barn owls remain on the same side of the mountains. The Rockies appear to significantly isolate the populations in the west, which, as a consequence, display lower genetic diversity than their counterparts to the east. Main conclusions The Rocky Mountains appear to constrain barn owl dispersal and gene flow. Our study supports the hypothesis that regional landscape barriers can shape gene flow and population structure even in highly mobile organisms.

Sequence variation in melanocortin-1-receptor and tyrosinase-related protein 1 genes and their relationship with melanin-based plumage trait expression in Lesser Kestrel (Falco naumanni) males - Margherita Corti; Stefano Podofillini; Matteo Griggio; Luca Gianfranceschi; Anne-Lyse Ducrest; Alexandre Roulin; Jacopo G. Cecere; Nicola Saino; Diego Rubolini (Journal of Ornithology, 2018)

Nocturnal, diurnal and bimodal patterns of locomotion, sibling interactions and sleep in nestling Barn Owls - Madeleine F. Scriba; Amélie N. Dreiss; Isabelle Henry; Paul Béziers; Charlène Ruppli; Estelle Ifrid; Pauline Ducouret; Arnaud Da Silva; Baudouin des Monstiers; Alexei L. Vyssotski; Niels C. Rattenborg; Alexandre Roulin (Journal of Ornithology, 2017)

Responsiveness to siblings’ need increases with age in vocally negotiating barn owl nestlings - Amélie N. Dreiss; Charlène A. Ruppli; Alice Delarbre; Christof Faller; Alexandre Roulin (Behavioral Ecology and Sociobiology, 2017)

MC 1R variants affect the expression of melanocortin and melanogenic genes and the association between melanocortin genes and coloration - Luis M. San‐Jose; Anne‐Lyse Ducrest; Valérie Ducret; Céline Simon; Hannes Richter; Kazumasa Wakamatsu; Alexandre Roulin (Molecular Ecology, 2017)
The melanocortin‐1 receptor ( MC 1R ) gene influences coloration by altering the expression of genes acting downstream in the melanin synthesis. MC 1R belongs to the melanocortin system, a genetic network coding for the ligands that regulate MC 1R and other melanocortin receptors controlling different physiological and behavioural traits. The impact of MC 1R variants on these regulatory melanocortin genes was never considered, even though MC 1R mutations could alter the influence of these genes on coloration (e.g. by decreasing MC 1R response to melanocortin ligands). Using barn owl growing feathers, we investigated the differences between MC 1R genotypes in the (co)expression of six melanocortin and nine melanogenic‐related genes and in the association between melanocortin gene expression and phenotype (feather pheomelanin content). Compared to the MC 1R rufous allele, responsible for reddish coloration, the white allele was not only associated with an expected lower expression of melanogenic‐related genes ( TYR , TYRP 1, OCA 2, SLC 45A2, KIT , DCT ) but also with a lower MC 1R expression and a higher expression of ASIP , the MC 1R antagonist. More importantly, the expression of PCSK 2 , responsible for the maturation of the MC 1R agonist, α‐melanocyte‐stimulating hormone, was positively related to pheomelanin content in MC 1R white homozygotes but not in individuals carrying the MC 1R rufous allele. These findings indicate that MC 1R mutations not only alter the expression of melanogenic‐related genes but also the association between coloration and the expression of melanocortin genes upstream of MC 1R. This suggests that MC 1R mutations can modulate the regulation of coloration by the pleiotropic melanocortin genes, potentially decoupling the often‐observed associations between coloration and other phenotypes.

Sex‐specific allelic transmission bias suggests sexual conflict at MC 1R - Valérie Ducret; Arnaud Gaigher; Céline Simon; Jérôme Goudet; Alexandre Roulin (Molecular Ecology, 2016)
Sexual conflict arises when selection in one sex causes the displacement of the other sex from its phenotypic optimum, leading to an inevitable tension within the genome – called intralocus sexual conflict. Although the autosomal melanocortin‐1‐receptor gene ( MC 1R ) can generate colour variation in sexually dichromatic species, most previous studies have not considered the possibility that MC 1R may be subject to sexual conflict. In the barn owl ( Tyto alba ), the allele MC 1 R WHITE is associated with whitish plumage coloration, typical of males, and the allele MC 1 R RUFOUS is associated with dark rufous coloration, typical of females, although each sex can express any phenotype. Because each colour variant is adapted to specific environmental conditions, the allele MC 1 R WHITE may be more strongly selected in males and the allele MC 1 R RUFOUS in females. We therefore investigated whether MC 1R genotypes are in excess or deficit in male and female fledglings compared with the expected Hardy–Weinberg proportions. Our results show an overall deficit of 7.5% in the proportion of heterozygotes in males and of 12.9% in females. In males, interannual variation in assortative pairing with respect to MC 1R explained the year‐specific deviations from Hardy–Weinberg proportions, whereas in females, the deficit was better explained by the interannual variation in the probability of inheriting the MC 1 R WHITE or MC 1 R RUFOUS allele. Additionally, we observed that sons inherit the MC 1 R RUFOUS allele from their fathers on average slightly less often than expected under the first Mendelian law. Transmission ratio distortion may be adaptive in this sexually dichromatic species if males and females are, respectively, selected to display white and rufous plumages.

Vocal communication regulates sibling competition over food stock - Amélie N. Dreiss; Florence Gaime; Alice Delarbre; Letizia Moroni; Mélissa Lenarth; Alexandre Roulin (Behavioral Ecology and Sociobiology, 2016)

Barn owl feathers as biomonitors of mercury: sources of variation in sampling procedures - Inês Roque; Rui Lourenço; Ana Marques; João Pedro Coelho; Cláudia Coelho; Eduarda Pereira; João E. Rabaça; Alexandre Roulin (Ecotoxicology, 2016)

Social huddling and physiological thermoregulation are related to melanism in the nocturnal barn owl - Amélie N. Dreiss; Robin Séchaud; Paul Béziers; Nicolas Villain; Michel Genoud; Bettina Almasi; Lukas Jenni; Alexandre Roulin (Oecologia, 2016)

Agricultural land use and human presence around breeding sites increase stress-hormone levels and decrease body mass in barn owl nestlings - Bettina Almasi; Paul Béziers; Alexandre Roulin; Lukas Jenni (Oecologia, 2015)

Morph-specific genetic and environmental variation in innate and acquired immune response in a color polymorphic raptor - Laura Gangoso; Alexandre Roulin; Anne-Lyse Ducrest; Juan Manuel Grande; Jordi Figuerola (Oecologia, 2015)

Effect of the MC 1R gene on sexual dimorphism in melanin‐based colorations - Luis M. San‐Jose; Anne‐Lyse Ducrest; Valérie Ducret; Paul Béziers; Céline Simon; Kazumasa Wakamatsu; Alexandre Roulin (Molecular Ecology, 2015)
Variants of the melanocortin‐1 receptor ( MC 1R ) gene result in abrupt, naturally selected colour morphs. These genetic variants may differentially affect sexual dimorphism if one morph is naturally selected in the two sexes but another morph is naturally or sexually selected only in one of the two sexes (e.g. to confer camouflage in reproductive females or confer mating advantage in males). Therefore, the balance between natural and sexual selections can differ between MC 1R variants, as suggest studies showing interspecific correlations between sexual dimorphism and the rate of nonsynonymous vs . synonymous amino acid substitutions at the MC 1R . Surprisingly, how MC 1R is related to within‐species sexual dimorphism, and thereby to sex‐specific selection, has not yet been investigated. We tackled this issue in the barn owl ( Tyto alba ), a species showing pronounced variation in the degree of reddish pheomelanin‐based coloration and in the number and size of black feather spots. We found that a valine (V)‐to‐isoleucine (I) substitution at position 126 explains up to 30% of the variation in the three melanin‐based colour traits and in feather melanin content. Interestingly, MC 1R genotypes also differed in the degree of sexual colour dimorphism, with individuals homozygous for the II MC 1R variant being 2 times redder and 2.5 times less sexually dimorphic than homozygous individuals for the VV MC 1R variant. These findings support that MC 1R interacts with the expression of sexual dimorphism and suggest that a gene with major phenotypic effects and weakly influenced by variation in body condition can participate in sex‐specific selection processes.

Information Retention During Competitive Interactions: Siblings Need to Constantly Repeat Vocal Displays - Amélie N. Dreiss; Charlène A. Ruppli; Sévrine Antille; Alexandre Roulin (Evolutionary Biology, 2015)

Pheomelanin-based colouration is correlated with indices of flying strategies in the Barn Owl - Motti Charter; Yossi Leshem; Ido Izhaki; Alexandre Roulin (Journal of Ornithology, 2015)

Natural selection in a postglacial range expansion: the case of the colour cline in the European barn owl - Sylvain Antoniazza; Ricardo Kanitz; Samuel Neuenschwander; Reto Burri; Arnaud Gaigher; Alexandre Roulin; Jérôme Goudet (Molecular Ecology, 2014)
Gradients of variation—or clines—have always intrigued biologists. Classically, they have been interpreted as the outcomes of antagonistic interactions between selection and gene flow. Alternatively, clines may also establish neutrally with isolation by distance ( IBD ) or secondary contact between previously isolated populations. The relative importance of natural selection and these two neutral processes in the establishment of clinal variation can be tested by comparing genetic differentiation at neutral genetic markers and at the studied trait. A third neutral process, surfing of a newly arisen mutation during the colonization of a new habitat, is more difficult to test. Here, we designed a spatially explicit approximate Bayesian computation ( ABC ) simulation framework to evaluate whether the strong cline in the genetically based reddish coloration observed in the European barn owl ( T yto alba ) arose as a by‐product of a range expansion or whether selection has to be invoked to explain this colour cline, for which we have previously ruled out the actions of IBD or secondary contact. Using ABC simulations and genetic data on 390 individuals from 20 locations genotyped at 22 microsatellites loci, we first determined how barn owls colonized Europe after the last glaciation. Using these results in new simulations on the evolution of the colour phenotype, and assuming various genetic architectures for the colour trait, we demonstrate that the observed colour cline cannot be due to the surfing of a neutral mutation. Taking advantage of spatially explicit ABC , which proved to be a powerful method to disentangle the respective roles of selection and drift in range expansions, we conclude that the formation of the colour cline observed in the barn owl must be due to natural selection.

Melanin‐based colour polymorphism responding to climate change - Alexandre Roulin (Global Change Biology, 2014)
Climate warming leads to a decrease in biodiversity. Organisms can deal with the new prevailing environmental conditions by one of two main routes, namely evolving new genetic adaptations or through phenotypic plasticity to modify behaviour and physiology. Melanin‐based colouration has important functions in animals including a role in camouflage and thermoregulation, protection against UV ‐radiation and pathogens and, furthermore, genes involved in melanogenesis can pleiotropically regulate behaviour and physiology. In this article, I review the current evidence that differently coloured individuals are differentially sensitive to climate change. Predicting which of dark or pale colour variants (or morphs) will be more penalized by climate change will depend on the adaptive function of melanism in each species as well as how the degree of colouration covaries with behaviour and physiology. For instance, because climate change leads to a rise in temperature and UV ‐radiation and dark colouration plays a role in UV ‐protection, dark individuals may be less affected from global warming, if this phenomenon implies more solar radiation particularly in habitats of pale individuals. In contrast, as desertification increases, pale colouration may expand in those regions, whereas dark colourations may expand in regions where humidity is predicted to increase. Dark colouration may be also indirectly selected by climate warming because genes involved in the production of melanin pigments confer resistance to a number of stressful factors including those associated with climate warming. Furthermore, darker melanic individuals are commonly more aggressive than paler conspecifics, and hence they may better cope with competitive interactions due to invading species that expand their range in northern latitudes and at higher altitudes. To conclude, melanin may be a major component involved in adaptation to climate warming, and hence in animal populations melanin‐based colouration is likely to change as an evolutionary or plastic response to climate warming.

Barn Owl (Tyto alba) breeding biology in relation to breeding season climate - Alexandre Chausson; Isabelle Henry; Bettina Almasi; Alexandre Roulin (Journal of Ornithology, 2014)

Efficiency and Significance of Multiple Vocal Signals in Sibling Competition - Charlène A. Ruppli; Amélie N. Dreiss; Alexandre Roulin (Evolutionary Biology, 2013)

Immune and Stress Responses Covary with Melanin-Based Coloration in the Barn Swallow - Nicola Saino; Luca Canova; Alessandra Costanzo; Diego Rubolini; Alexandre Roulin; Anders Pape Møller (Evolutionary Biology, 2013)

Pleiotropy in the melanocortin system: expression levels of this system are associated with melanogenesis and pigmentation in the tawny owl ( Strix aluco ) - Guillaume Emaresi; Anne‐Lyse Ducrest; Pierre Bize; Hannes Richter; Celine Simon; Alexandre Roulin (Molecular Ecology, 2013)
The adaptive function of melanin‐based coloration is a long‐standing debate. A recent genetic model suggested that pleiotropy could account for covariations between pigmentation, behaviour, morphology, physiology and life history traits. We explored whether the expression levels of genes belonging to the melanocortin system ( MC 1R , POMC , PC 1/3 , PC 2 and the antagonist ASIP ), which have many pleiotropic effects, are associated with melanogenesis (through variation in the expression of the genes MITF , SLC 7A11, TYR , TYRP 1 ) and in turn melanin‐based coloration. We considered the tawny owl ( Strix aluco ) because individuals vary continuously from light to dark reddish, and thus, colour variation is likely to stem from differences in the levels of gene expression. We measured gene expression in feather bases collected in nestlings at the time of melanin production. As expected, the melanocortin system was associated with the expression of melanogenic genes and pigmentation. Offspring of darker reddish fathers expressed PC 1/3 to lower levels but tended to express PC 2 to higher levels. The convertase enzyme PC 1/3 cleaves the POMC prohormone to obtain ACTH , while the convertase enzyme PC 2 cleaves ACTH to produce α‐melanin‐stimulating hormone (α‐ MSH ). ACTH regulates glucocorticoids, hormones that modulate stress responses, while α‐ MSH induces eumelanogenesis. We therefore conclude that the melanocortin system, through the convertase enzymes PC 1/3 and PC 2, may account for part of the interindividual variation in melanin‐based coloration in nestling tawny owls. Pleiotropy may thus account for the covariation between phenotypic traits involved in social interactions (here pigmentation) and life history, morphology, behaviour and physiology.

Ring recoveries of dead birds confirm that darker pheomelanic Barn Owls disperse longer distances - Alexandre Roulin (Journal of Ornithology, 2013)

Melanin-based colour polymorphism signals aggressive personality in nest and territory defence in the tawny owl (Strix aluco) - Arnaud Da Silva; Valentijn van den Brink; Guillaume Emaresi; Ester Luzio; Pierre Bize; Amélie N. Dreiss; Alexandre Roulin (Behavioral Ecology and Sociobiology, 2013)

Corticosterone Promotes Scramble Competition Over Sibling Negotiation in Barn Owl Nestlings (Tyto alba) - Charlène A. Ruppli; Bettina Almasi; Amélie N. Dreiss; Marine Battesti; Lukas Jenni; Alexandre Roulin (Evolutionary Biology, 2012)

Condition-dependent expression of melanin-based coloration in the Eurasian kestrel - Romain Piault; Valentijn van den Brink; Alexandre Roulin (The Science of Nature, 2012)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

Pale and dark reddish melanic tawny owls differentially regulate the level of blood circulating POMC prohormone in relation to environmental conditions - Alexandre Roulin; Guillaume Emaresi; Pierre Bize; Julien Gasparini; Romain Piault; Anne-Lyse Ducrest (Oecologia, 2011)

Habitat, breeding performance, diet and individual age in Swiss Barn Owls (Tyto alba) - Caroline Frey; Caroline Sonnay; Amélie Dreiss; Alexandre Roulin (Journal of Ornithology, 2011)

Eumelanin-based coloration and fitness parameters in birds: a meta-analysis - Joël Meunier; Susana Figueiredo Pinto; Reto Burri; Alexandre Roulin (Behavioral Ecology and Sociobiology, 2011)

Indirect Costs of Parasitism are Shaped by Variation in the Type of Immune Challenge and Food Availability - Pierre Bize; Romain Piault; Julien Gasparini; Alexandre Roulin (Evolutionary Biology, 2010)

Darker eumelanic barn owls better withstand food depletion through resistance to food deprivation and lower appetite - Amélie Dreiss; Isabelle Henry; Charlène Ruppli; Bettina Almasi; Alexandre Roulin (Oecologia, 2010)

Wildflower areas within revitalized agricultural matrices boost small mammal populations but not breeding Barn Owls - Raphaël Arlettaz; Markus Krähenbühl; Bettina Almasi; Alexandre Roulin; Michael Schaub (Journal of Ornithology, 2010)

Sex‐dependent selection on an autosomal melanic female ornament promotes the evolution of sex ratio bias - Alexandre Roulin; Res Altwegg; Henrik Jensen; Ingelin Steinsland; Michael Schaub (Ecology Letters, 2010)
Ecology Letters (2010) 13: 616–626 Abstract Sex‐dependent selection often leads to spectacularly different phenotypes in males and females. In species in which sexual dimorphism is not complete, it is unclear which benefits females and males derive from displaying a trait that is typical of the other sex. In barn owls ( Tyto alba ), females exhibit on average larger black eumelanic spots than males but members of the two sexes display this trait in the same range of possible values. In a 12‐year study, we show that selection exerted on spot size directly or on genetically correlated traits strongly favoured females with large spots and weakly favoured males with small spots. Intense directional selection on females caused an increase in spot diameter in the population over the study period. This increase is due to a change in the autosomal genes underlying the expression of eumelanic spots but not of sex‐linked genes. Female‐like males produced more daughters than sons, while male‐like females produced more sons than daughters when mated to a small‐spotted male. These sex ratio biases appear adaptive because sons of male‐like females and daughters of female‐like males had above‐average survival. This demonstrates that selection exerted against individuals displaying a trait that is typical of the other sex promoted the evolution of specific life history strategies that enhance their fitness. This may explain why in many organisms sexual dimorphism is often not complete.

Melanin-based coloration covaries with ovary size in an age-specific manner in the barn owl - Alexandre Roulin (The Science of Nature, 2009)

Covariation between eumelanic pigmentation and body mass only under specific conditions - Alexandre Roulin (The Science of Nature, 2009)

Isolation and characterization of major histocompatibility complex (MHC) class II B genes in the Barn owl (Aves: Tyto alba) - Reto Burri; Hélène Niculita-Hirzel; Alexandre Roulin; Luca Fumagalli (Immunogenetics, 2008)

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Intra-individual variation in body temperature and pectoral muscle size in nestling Alpine swifts Apus melba in response to an episode of inclement weather - Pierre Bize; Aurélie Klopfenstein; Caroline Jeanneret; Alexandre Roulin (Journal of Ornithology, 2007)

Sexual selection in genetic colour-polymorphic species: a review of experimental studies and perspectives - Alexandre Roulin; Pierre Bize (Journal of Ethology, 2007)

Analysis of genetic parentage in the tawny owl (Strix aluco) reveals extra-pair paternity is low - Verena Saladin; Mathias Ritschard; Alexandre Roulin; Pierre Bize; Heinz Richner (Journal of Ornithology, 2007)

A link between eumelanism and calcium physiology in the barn owl - Alexandre Roulin; Tom Dauwe; Ronny Blust; Marcel Eens; Michel Beaud (The Science of Nature, 2006)

Demographic effects of extreme winter weather in the barn owl - Res Altwegg; Alexandre Roulin; Matthias Kestenholz; Lukas Jenni (Oecologia, 2006)

Oxygen consumption in offspring tawny owls Strix aluco is associated with colour morph of foster mother - Alexandre Roulin; Pierre Bize; Nathalie Tzaud; Matteo Bianchi; Pierre-Alain Ravussin; Philippe Christe (Journal of Ornithology, 2005)

Proximate basis of the covariation between a melanin-based female ornament and offspring quality - Alexandre Roulin (Oecologia, 2004)

Why do melanin ornaments signal individual quality? Insights from metal element analysis of barn owl feathers - Manfred Niecke; Sven Rothlaender; Alexandre Roulin (Oecologia, 2003)

Indiscriminate nursing in communal breeders: a role for genomic imprinting - Alexandre Roulin; Reinmar Hager (Ecology Letters, 2003)
In several communally nesting mammal species, females indiscriminately nurse each others' offspring. Previous hypotheses have suggested that the inability to recognize one's own young during lactation is the result of costs incurred from recognition errors. Here, we propose an alternative hypothesis based on sexual conflict theory and genomic imprinting. In polygynous species, males copulate with several females that may later breed communally. Under such conditions, males benefit from indiscriminate nursing of all their offspring and the reduced risk of female infanticide. This may have selected for paternally expressed genes that suppress kin recognition during lactation.

Covariation between egg size and rearing condition determines offspring quality: an experiment with the alpine swift - Pierre Bize; Alexandre Roulin; Heinz Richner (Oecologia, 2002)